Auckland district health board radiology service improvement: An after hours ultrasound service pilot study. Issue 1 (21st February 2017) - Gerrie, Samantha; Sim, Jenny; Winstone, Tim; Milne, David; Modahl, Lucy; Bagnall, Carol; Curin, Raewyn; Metcalfe, Julia; O'Carroll, Nicola
Abstract: Introduction: The aim of the study was to improve acute diagnostic workflow by provision of a dedicated sonographer‐lead after hours ultrasound (US) service. Methods: Data on patients referred for the four most common referrals was obtained retrospectively over a 3‐month period both prior to, and during, a 6‐month sonographer‐lead after hours US service. The primary outcome measure was mean time from referral to US exam. The secondary outcome measure was the mean number of days between US referral and discharge. Results: There was a statistically significant decrease in the mean referral to exam time of three of the four referral groups and a statistically significant decrease in the number of days between US referral and discharge in the post‐intervention group compared with the pre‐intervention group. Discussion: There was a clear early indication of improvement in patient safety and ability to provide effective and efficient care. Our recommendation is to use this data to provide the basis for application for funding for a permanent sonographer‐lead after hours US service.